Network Nerves Mock Backpropagation Prediction Graduation Student Elementary School With Practice Values Exam - Rahmawati Sunaryo, Azzahra; Abelia, Nevanda; Hastono, Tri; Pratisto, Eko Harry (Lembaga Penelitian dan Pengabdian Mayarakat (LPPM) Universitas PGRI Yogyakarta, 2023)
The backpropagation method is a computer technique to help predict and sort data. This method is usually used to change the connection between parts of the computer's brain in the hidden layer. Meanwhile, the Nervous System Network (ANN) is an information-processing system that is very similar to the function of human brain cells. Value is a benchmark for a student's graduation, if the student's score is getting better, the more opportunities for the student's graduation. In predicting this pass using the method of Artificial Neural Networks (ANN), namely Backpropagation, and using Matlab software with the MSE (Mean Square Error) result of 0.099512.